(untitled) (Medico Legal Update, 2021)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. The chronic hyperglycemia of diabetes is associated with long-term damage, dysfunction, and failure of various organs, especially the eyes, kidneys, nerves, heart, and blood vessels; Podocalyxin is the major sialoprotein in the glycocalyx of glomerular podocytes, podocalyxin was found in the blood vessels of several organs. Objective: The aim of the present study was to elevate serum podocalyxin and some biochemical parameters in diabetic patients compare with healthy group. Method: The present case-control study included 90 participants divided into two groups: 60 patients with diabetes mellitus (40 males and 20 females; aged 49.87 ±8.089 yr.) study group and 30 (20 males and 10 females; aged 48.27±6.335 yr.) a healthy group (control group). Podocalyxin (PODXL) and insulin measured using the ELISA kit. Anthropometric were measured fasting serum glucose levels and lipid profile were determined by photometric method. Result: The mean serum podocalyxin levels was significantly increase in patients with diabetes mellitus Vs. healthy control group (26.24±2.11ngVs. 17.45±1.57ngrespectively, p<0.001), BMI was significantly increased in patients diabetes mellitus Vs. healthy control group (29.766±3.225 Vs. 23.756±0.77 respectively, p<0.001) also the mean fasting insulin level was higher in patients with diabetes mellitus than the healthy control group (7.23±1.26 Vs. 5.05±1.14 respectively, p<0.001), HOMA-IR significantly increased in patients with diabetes mellitus Vs. healthy control group (2.65±0.77 Vs. 1.16±0.25 respectively, p<0.001) but the mean of HOMA-? in patients with diabetes mellitus was significantly lower than the healthy control group (35.30±13.83 Vs. 61.91±19.87 respectively, p<0.001), lipid profile include TG, TC, LDL-C, VLDL-C significant increased in patients with diabetes mellitus compared with healthy control group (211.50±88.02 Vs. 116.87±38.43, p<001), (240.13±56.20 Vs. 141.43±33.34, p<0.001), (161.87±56.39 Vs. 65.82±30.97, p<0.001), (42.30±17.60 Vs. 23.37±7.68, p<0.001) respectively except HDL-C were significantly decreased in patients with diabetes mellitus than the healthy control group (33.83±9.02 Vs. 52.23±7.08 respectively, p<0.001), Patients with diabetic mellitus have significantly higher serum podocalyxin levels than the controls. Podocalyxin levels positively significantly correlated with BMI, FSG, Insulin, HbA1c and HOMAIR levels while HOMO-? significant negative correlation respectively with podocalyxin levels. podocalyxin may be a promising biomarker in patients with diabetes mellitus. Conclusion: Podocalyxin may be a promising biomarker in patients with diabetes mellitus and can be used as a high risk markers for CVDs in DM patients.